(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The environment has always been the source of the energy of life. It is from natural resources that peoples receive a resource to continue their existence. This article discusses topical issues of environmental protection and environmental safety, the role of public administration and their ways in solving these problems.